PENERAPAN AUGMENTED REALITY SEBAGAI MEDIA PROMOSI FURNITURE MENGGUNAKAN METODE MARKERLESS TRACKING - Septa (Journal of Research and Publication Innovation, 2023)
This research aims to implement Augmented Reality (AR) technology using markerless tracking as a promotional tool for furniture. AR enables consumers to view three-dimensional models of furniture products through the camera of an Android device without the need to physically visit a store. The markerless tracking method allows object detection without the requirement of specific markers and enables automatic marker formation. The results indicate that implementing AR with markerless tracking is effective in promoting furniture products, providing an interactive experience for consumers, and facilitating access without the need for physical visits to the store.